The effect of capacity of acid soils developed on basalt in Daher Al-jabal area in al Sowida Governorate changes in pH on the cation exchange (Damascus University Journal of agriculture sciences, 2025)
The research was conducted in  Daher al-jabal area in al-Sowaida during the years 2021-2022, with the aim of studying the effect of soil pH change on the cationic exchange capacity values of acidic soils developed on basalts in the Daher al-jabal area in al-Sowida governorate, in addition to characterizing the soil of this area physically, chemically, and fertility; Where I prepared three profiles representing the studied area, and soil samples were collected from the horizons of each profile in a systematic manner and were analyzed in the laboratory. The results led to the following:The studied soils were characterized by a capacity of cation exchange between medium and very high, and the base cations dominated the surfaces of the adsorption complexes, and the calcium and magnesium cations came in the forefront.Received: 19/6/2023Accepted: 10/8/2023 Copyright: Damascus University- Syria, The authors retain the copyright undera CC BY- NC-SA The studied showed an anion exchange capacity, that may be due to the presence of some variable charge colloids, or to the effect of the edge of some minerals with a permanent charge. Also, there was a change in the values of the cation exchange capacity when the pH was changed, as the values decreased with a decrease in the pH degree.The tendency of soil pH to acidity, and this reflects the soil components, and the leaching processes of some components, especially alkali and alkaline earth elements.The soil content of trace elements )Fe- Mn- Zn- Cu (is ranging between low to very high .
Keywords: Basaltic; Cation exchange capacity; Micro elements; Acid; Daher Al-jabal; Anion Exchange Capacity